Limbo or leverage? Asylum waiting and refugee integration - Mattias Engdahl; Olof Rosenqvist; Olof Åslund (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
We study the impact of asylum waiting, exploiting a rapid increase in processing times for asylum seekers to Sweden in 2014. Longer waiting slows down the integration process and affects labor market outcomes for an extended period. Accumulated earnings during the first four years after application are 2.3 percent lower per added month of waiting. The impact appears to be due to delay rather than negative effects of waiting per se. There is no evidence of detrimental effects on psychiatric or other forms of health. From the date of being granted asylum, people who have waited longer perform better in the labor market and exhibit higher entry into more advanced language training and labor market measures.
Keywords: F22; J15; J68; 330; Asylum waiting; labor market; health